Possibilities of Therapeutic and Prophylactic Tactics in Management of Benign Prostatic Hyperplasia in Tuberculosis Patients - Z. R. Rashidov; Sh. T. Mukhtаrov; S. I. Аzimov (Туберкулез и болезни лёгких)
The objective: to assess the severity of symptoms of urinary dysfunction in tuberculosis patients with benign prostatic hyperplasia (BPH) and determine the effectiveness of comprehensive therapeutic and preventive measures aimed at their elimination as well as the possibility of their combination with anti-tuberculosis therapy.Subjects and Methods. 447 men with various localizations of tuberculosis at the age from 20 to 96 years old were examined. The questionnaire we used included questions regarding lower urinary tract symptoms, urinary tract infection, involuntary urination, and male genital disorders. The assessment involved comprehensive clinical and laboratory evaluation, including objective examination, laboratory and echographic tests of genitourinary organs.Results. According to assessment results, among 447 male tuberculosis patients, 88 (19.7%) were diagnosed with benign prostatic hyperplasia which indicated a large proportion of older men with various forms of tuberculosis. Analysis of the structure of tuberculosis clinical forms showed the highest frequency of benign prostatic hyperplasia in patients with infiltrative pulmonary tuberculosis (51.1%) and bone and joint tuberculosis (26.1%). Medical treatment (tamsulosin 0.4 mg once a day for 3 months) in 66 patients was highly effective – up to 80.3%.